Pengaruh Kualitas Produk, Harga, Pengalaman Pelanggan terhadap Loyalitas pada Produk Lipstik Wardah di Toko Riska - Serli Sela Yolanda; Diana Ambarwati; Nurali Agus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research discusses the influence of product quality, price and consumer experience on Wardah lipstick users. The aim of this research is to determine and explain the influence of product quality, price and customer experience on Wardah lipstick users. This research was conducted from 1 April 2023 to 30 June 2023 with a population of 176 consumers. The sample who repeatedly purchased Wardah lipstick at the Riska store was 122 consumers from 1 April 2023 to 30 June 2023. The sampling method for this research used purposive sampling.The results of the research are that product quality has a partial effect on Wardah lipstick product loyalty at the Riska Store with a significance value of 0.000 < 0.05. Price has a partial effect on Wardah lipstick product loyalty at the Riska Store with a significance value of 0.000 < 0.05. Customer experience partially influences Wardah lipstick product loyalty at the Riska Store with a significance value of 0.000 < 0.05. Product quality, price, customer experience have a significant effect on Wardah lipstick product loyalty at the Riska Store simultaneously with a significance value of 0.000 < 0.05.